Confirmatory factor analysis : the validation of mathematical values inculcation among secondary school mathematic teachers in north-eastern Nigeria - Liman, Mukhtar Alhaji; Nordin, Mohamad Sahari; Shittu, Ahmed Tajudeen (IIBR(Institute of Interdisciplinary Business Research, 2011)
The use of Confirmatory Factor Analysis (CFA) on researches based on certain theoretical frame-work in both social sciences and education cannot be over-emphasized, as such this study employed the confirmatory factor analysis in an attempt to validates the mathematical values inculcation path measurement model among secondary schools mathematics teachers in the north-eastern part of Nigeria with aim of finding whether or not the data fit the model for the purpose of inference generalization. The preliminary sample size for the study is (n=101) secondary schools mathematics teachers that are involved in the study. The instrument for the data collection was a Questionnaire with some of the items designed and adopted. Amos graphic a statistical tool for structural equation modeling was used in finding the fit adequacy of the mathematical values path measurement model which shows the following fit-indices: NormX2 = 1.993, CFI = 0.903 and RMSEA = 0.099 all of which indicated the goodness of fit of the model except for RMSEA which lies within the range of mediocre. The purpose of this study is to acquaint secondary schools mathematics teachers to the need of inculcation of mathematical values in mathematics teaching and learning with sole objective of enhancing better understanding of mathematical concepts. The study is guided by the following research question and hypothesis: Is there any significant correlation between mathematics teaching and learning and its components of values inculcation? The understanding of mathematics teaching and learning is not significantly correlated to the inculcation of the mathematics conceptual values.